PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL BERBASIS CANVA PADA MATA PELAJARAN IPAS KELAS V SDN 02 SUNGAI RUMBAI - M. Anggrayni; Wiwik Okta Susilawati; Muslimatun Hasanah (STKIP Subang, 2024)
This research aims to overcome several problems that occur by developing more interesting learning media, so that it can improve student learning outcomes. The media that will be developed is digital comic-based learning media which aims to attract students' interest in improving learning outcomes. This research uses the type of research and development R&D (Research and Development). The R&D (Research and Development) research method is a research method used to produce certain products and test the effectiveness of these products. Apart from that, Research and Development is also a research method for developing and testing products that will later be developed in the world of education. Based on the problems described in the background, this research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The ADDIE model is a systematic learning design model. The ADDIE model has five development stages, namely: Analyze, Design, Development, Implementation, Evaluation. In developing ADDIE there are five procedural stages, namely Analysis, Design (rancangan), Development (pengembangan), Implementation (implementasi) and Evaluation (evaluasi). Test the effectiveness of Canva-based digital comic learning media in science subjects to support the independent curriculum for class V elementary schools, seen from student learning outcomes. Where the effectiveness sheet is in the form of a test containing questions, based on the effectiveness test that was carried out in class V of SDN 02 Sungai Rumbai, namely with an average score of 92% in the very effective category. The results of the analysis of 23 students who completed and 2 who did not complete, with a total of 25, the number of students who completed was 23 divided by the number of students 25 times 100, the result was 92% categorized as very effective.